Analisis Kinerja Keuangan Menggunakan Metode Altman Z-Score terhadap Harga Saham: (Studi Empiris pada Perusahaan Subsektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Rani Hairunnisa Rahmawati; Retno Fuji Oktaviani (STIKes Ibnu Sina Ajibarang, 2024)
Share prices experience fluctuations that occur every year in banking companies listed on the Indonesia Stock Exchange in the 2019-2023 period. This research aims to determine the effect of Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest and Taxes to Total Assets, and Market Value Equity to Total Liabilities on Share Prices in Banking Companies listed on the Indonesia Stock Exchange for the 2019-2023 period. . The population of the Indonesian Stock Exchange is 47 companies. The samples taken in this research were 9 banking companies using purposive sampling technique. The analytical tool used is multiple linear analysis which was tested using Statistical Product and Service Solution (SPSS) version 26. The results of this research show that Working Capital to Total Assets has a negative effect on Stock Prices, Retained Earning to Total Assets has a positive effect on Stock Prices , while Earnings Before Interest and Taxes to Total Assets and Market Value Equity to Total Liabilities have no effect on share prices.